The calcium application to control yellow latex in mangosteen fruit (Garcinia mangostana). Issue 4 (July 2021) - Yuniarti, S; Lestari, S; Hadiatry, M C; Purba, R
Abstract: The main problem of mangosteen production is yellow latex in the rind and aril of the mangosteen fruit. The yellow latex occurs from the yellow latex channel's rupture and contaminates the arils or mangosteen rind. The rupture is thought due to the lack of calcium in the epithelial cell walls of the yellow latex ducts. The present study aimed to determine the effect of calcium in reducing yellow latex in the mangosteen fruit. The study was conducted in Luhur Jaya Village, Lebak Regency of Banten Province. The study used a randomized block design, consisting of 6 treatments and 5 replications with treatment P0=control, P1=dose of calcium/dolomite lime 2 kg/tree, P2=dose of calcium/dolomite lime 3 kg/tree, P3=dose of calcium/dolomite lime 4 kg/tree, P4=dose of calcium/dolomite lime 5 kg/tree, P5=dose of calcium/dolomite lime 6 kg/tree. The calcium was given when the mangosteen plant started to flower. From the results, the application of calcium using dolomite (CaMg(CO3)2) reduced yellow latex contamination in mangosteen rind at doses of 5 kg/tree. All doses of calcium applied (2, 3, 4, 5, and 6 kg/tree) reduced yellow latex contamination in arils. The application of calcium with dolomite (CaMg(CO3)2) did not affect fruit weight and dotted on mangosteen.